2020
DOI: 10.3390/ijms21041238
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Impaired In Vitro Ovine Early Developmental Oocyte Competence

Abstract: Introduction: Bisphenol A (BPA) is a widespread compound in the plastic industry that is especially used to produce baby bottles, food packaging and metal cans. BPA, an endocrine disruptor, leads to alterations in reproductive function and therefore has been banned from the food industry. Unregulated BPA analogues, particularly Bisphenol S (BPS), have emerged and are now used in the plastic industry. Thus, this study aimed to examine the acute effects of low and environmental doses of BPS on ewe oocyte quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 83 publications
(117 reference statements)
2
17
0
Order By: Relevance
“…Indeed, a sample can be contaminated by BPS but not BPSG. Previous data on ewe oocyte quality reported a detrimental effect of BPS at a concentration as low as 10 nM [45], which corresponds to the level of BPSG reported in female follicular fluids in the present study. Therefore, these data raise the issue of human oocyte sensitivity to BPS treatment, which may be similar to the sensitivity observed in the ovine model.…”
Section: Bps In Follicular Fluidsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, a sample can be contaminated by BPS but not BPSG. Previous data on ewe oocyte quality reported a detrimental effect of BPS at a concentration as low as 10 nM [45], which corresponds to the level of BPSG reported in female follicular fluids in the present study. Therefore, these data raise the issue of human oocyte sensitivity to BPS treatment, which may be similar to the sensitivity observed in the ovine model.…”
Section: Bps In Follicular Fluidsupporting
confidence: 90%
“…Moreover, as mentioned above, the BPS effects appeared to differ depending on the species. Indeed, HGC appear to be more sensitive to BPS treatment compared to other animal models, including swine [45] and cow GC [42]. On the contrary, HGC are similar in terms of sensitivity to progesterone secretion with ewe GC.…”
Section: Bps Reduced Hgc Progesterone and Oestradiol Secretionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some studies indicate that Bisphenol A (BPA) analogues such as Bisphenol S (BPS) which are currently unregulated, and used in the plastic industry, are not safe alternatives for BPA. In ovines, BPS exposure impairs oocyte development competence with blastocyte rate reduction being observed [ 5 ]. In human granulosa cells, the administration of BPS leads to reduced secretion of oestradiol and progesterone which are observed after 48 h of exposure suggesting that the effects of chronic exposure might be similar [ 6 ].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Studies have shown that BPS exposure significantly reduced testosterone secretion in mouse fetal testes (Eladak et al, 2015). BPS exposure of female mice caused a significant reduction in egg number and impaired oocyte quality and developmental competence (Desmarchais et al, 2020). BPS exposure induced oxidative stress and adipocyte differentiation leading to obesity (Ahmed & Atlas, 2016; Boucher, Ahmed, & Atlas, 2016).…”
Section: Introductionmentioning
confidence: 99%